Design of a high-performance single-phase offline UPS with reduced switching time - Pinto, Delfim A. (2012)
A high performance single phase offline UPS with reduced switching time is proposed in the present paper. The proposed UPS can protect loads from supply outage, overvoltage and undervoltage. A bidirectional DC-DC converter takes part of the presented model, in order to reduce the system size. Thus, the converter has the capability to charge the battery and to keep a regulated voltage for the inverter’s DC-link. In order to provide a regulated output voltage for any type of load, a PWM (Pulse-Width Modulation) inverter with a multi-loop control strategy, using capacitor current as feedback variable, is also developed. By using the sliding window method, to detect long period voltage disturbances in real time, the switching time between mains and UPS can be significantly reduced. Moreover, simulation and practical results in different mains conditions are analyzed.